Building-integrated greenhouses raise energy co-benefits through active ventilation systems. (15th January 2022) - Muñoz-Liesa, Joan; Royapoor, Mohammad; Cuerva, Eva; Gassó-Domingo, Santiago; Gabarrell, Xavier; Josa, Alejandro
Abstract: Buildings and greenhouses consume vast amounts of energy and natural resources for heating and ventilation. It is still unclear how the synergetic effect of combining greenhouses and buildings' forced waste airflows could improve both systems' energy efficiency. This study quantified the energy recovery potential of exchanging airflows in a rooftop greenhouse (iRTG) integrated with an office building HVAC system in a Mediterranean climate. Using monitored and calibrated energy model data, the results showed that the iRTG can act as a solar collector and as a sink for a building's low-grade waste heat. The magnitude of harvested thermal energy that could be recirculated into the building by the integrated HVAC system was 205.2 kWh/m 2 y −1 and was limited by greenhouse low transmissivity (54%). The magnitude of building exhaust air was 198 kWh/m 2 y −1 at temperatures sufficient to heat and cool the iRTG. Compared to a passive ventilated configuration, the integration of active ventilation strategies doubled the energy benefits. Building ventilation requirements directly determined building and greenhouse waste flows and energy benefits, which increased by 63.1% when air changes per hour moved from 1.59 to 3.16. Overall, this demonstrates that greenhouse and building functionalities could be coupled to contribute to urban circularity and sustainability. Graphical abstract: Image 1 Highlights: A greenhouse integrated within the building HVAC system was investigated. Real and modelling data was combined to quantify energy co-benefits. The iRTG recycled 143 kWh/m 2 ·y of sensible heat from building waste heat. The iRTG solar capacity conveyed 205 kWh/m 2 ·y of sensible heat to the building. Active strategies doubled the energy benefits compared to passive mechanisms.